ASSESSMENT OF SOME PHYSICOCHEMICAL PROPERTIES AND HEAVY METALS IN WATER FROM FARMLANDS AROUND MAHANGA LAKE, BALI LOCAL GOVERNMENT AREA OF TARABA STATE, NIGERIA - Dowell Bartimaeus, Farimani; Modibbo Umar, Usman; Malgwi Daniel, Wasinda; Umar Mohammed, Abubakar (FUDMA Journal of Sciences, 2025)
Water quality in agricultural landscapes is increasingly threatened by physicochemical pollutants and heavy metals arising from farming practices and anthropogenic activities. These contaminants pose serious risks to ecosystem health and human safety, particularly in rural communities that rely directly on natural water bodies for drinking, irrigation, and domestic use. This study assessed the physicochemical properties and heavy metal concentrations in water from farmlands around Mahanga Lake, Bali Local Government Area, Taraba State, Nigeria. Water samples were collected from four cardinal points (North, South, East, West) and analyzed using standard methods. Physicochemical parameters (pH, Temperature, Electrical Conductivity, Total Suspended Solids, Total Dissolved Solids, Turbidity) were measured with appropriate meters, while heavy metals (Cd, Cr, Cu, Ni, Pb) were determined using Atomic Absorption Spectroscopy. Results revealed that pH (5.7–6.8), TSS (190–210 mg/L), and turbidity (32–38 NTU) did not meet WHO drinking water standards. Heavy metal analysis showed that Cr (0.063–0.085 mg/L) and Pb (0.048–0.071 mg/L) concentrations exceeded permissible WHO limits, while Cd (0.015–0.028 mg/L), Cu (0.13–0.18 mg/L), and Ni (0.0008–0.001 mg/L) were within acceptable ranges. Pearson’s correlation analysis indicated a strong positive relationship between TSS and turbidity (r = 0.996), and between Cr and Pb (r = 0.955), suggesting common pollution sources. The study concludes that the lake water is unsuitable for drinking and recommends continuous monitoring, public awareness on water safety, and implementation of remediation strategies to reduce pollutant influx from agricultural and anthropogenic activities.
Keywords: Heavy metals, Physicochemical properties, Mahanga lake, Water quality, Environmental toxicity